(3bUjOI GdHGLi aj GdYbGFOs - (3Ydj Hf eMeO Hf YHO GdQMef Hf NWGH, YdGA GdOjf GdHGLj,J (B714 (3g` s ((3ecI GdecQeI s)
(3ChdgG (B:s
(3jbhd CVYa GdYjO GdQGLi eZaQI Ydi Hf GdHGLi GdMeO ddg Ydi GdJhajb dage eG Cdge ef JMbjb s
(3BNQgG (B:s
(3Udi Ydjg QHfG hSdeG eG dG M aLQ WGdY hcQekG hBdg hUMHg GdCNHGQ GdWjHjf GdSGOI GdCWgGQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B334 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B208s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds